2016
DOI: 10.1371/journal.pntd.0005126
|View full text |Cite
|
Sign up to set email alerts
|

Serological and Virological Evidence of Crimean-Congo Haemorrhagic Fever Virus Circulation in the Human Population of Borno State, Northeastern Nigeria

Abstract: BackgroundDespite several studies on the seroprevalence of antibodies against Crimean-Congo Haemorrhagic Fever virus (CCHFV) from humans and cattle in Nigeria, detailed investigation looking at IgG and IgM have not been reported. Additionally, there have been no confirmed cases of human CCHFV infection reported from Nigeria.Principal FindingsSamples from sera (n = 1189) collected from four Local Government Areas in Borno State (Askira/Uba, Damboa, Jere and Maiduguri) were assessed for the presence of IgG and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 39 publications
4
36
2
Order By: Relevance
“…Serologic and virologic evidence of CCHFV in humans has been reported in Nigeria (11). However, to our knowledge, CCHFV presence among domestic animals in the country has not been documented since the studies of Causey et al (3) and Umoh et al (4) conducted >3 decades ago.…”
Section: Discussionmentioning
confidence: 90%
“…Serologic and virologic evidence of CCHFV in humans has been reported in Nigeria (11). However, to our knowledge, CCHFV presence among domestic animals in the country has not been documented since the studies of Causey et al (3) and Umoh et al (4) conducted >3 decades ago.…”
Section: Discussionmentioning
confidence: 90%
“…However, despite several studies on the seroprevalence of antibodies against CCHFV from humans and animals in Nigeria, detailed investigation demonstrating the presence of IgG and IgM antibodies to the virus have not been reported until recently [20]. This study reported prevalence rates of IgG and IgM antibodies to be 10.6% and 3.5% respectively.…”
Section: Introductionmentioning
confidence: 56%
“…In addition to having high fatality rates, some also cause permanent disability, such as hearing loss following Lassa fever, or blindness after Rift Valley fever [10]. In Nigeria, there are reports from literature of serological and virological evidence of AHF virus activity in certain parts of the country among humans and animals [11][12][13][14][15][16][17][18][19][20]. Previous virological and serological surveys in Nigeria have revealed the presence of human and animal infections by some of the viruses associated with haemorrhagic fevers [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the ability to contain even known emerging viruses such as Ebola virus in wildlife is currently not possible. Furthermore, the management of diseases that involve livestock, such as RVF and CCHF, pose problems in that conventional vaccines are not suited for use in these environments. A major limitation of conventional vaccination is the requirement for individual inoculation of each animal – a costly and impractical strategy for the target/reservoir species of those animals frequently involved in the emergence of high‐risk pathogens .…”
Section: Future Perspectivesmentioning
confidence: 99%